Pediatric vestibular testing: Tolerability of test components in children. (October 2018) - Ciolek, Peter J.; Kang, Elise; Honaker, Julie A.; Woodson, Erika A.; Hopkins, Brandon S.; Anne, Samantha
Abstract: Introduction: Objective of the study is to define rates of successful completion of components of pediatric vestibular testing (VT). Methods: Retrospective review of VT performed on patients less than 18 years of age from 2004 to 2015. Results: 188 pediatric patients (mean age: 13.9 ± 3.56 years old, range 2–17 years) underwent testing. Thirty-five (18.6%) had abnormal test results. Pediatric patients unable to complete all aspects of VT could still complete an average of 7.9 ± 4.0 of 12 test components. The optokinetic tracking test was the most commonly omitted component of the vestibular tests. In a multivariate analysis, failure to perform Nylen-Barany positional testing (χ 2 27.5, p < 0.0001) or Dix-Hallpike (5.66, p = 0.0174) testing was associated with inability to obtain final diagnosis on VT. Conclusions: Interpretable VT may be obtained in most children, even in those that do not tolerate the full testing protocol. Spontaneous and gaze-evoked nystagmus testing maybe considered as part of initial testing protocol before attempting less well-tolerated components such as bithermal calorics or components that require VNG goggles.